Growth Inhibition of Aspergillus spp. by Endophytic Bacteria - Dwi N. Susilowati; Untung Haryono (Jurnal AgroBiogen, 2018)
Aspergillus spp. (A. niger, A. flavus, and A. fumigatus) contaminate food commodities through production of secondary metabolites (mycotoxins) and aspergillosis, and thus pose severe hazard to human and animal health. Hence, the inhibition of mycotoxin-producing fungi on agricultural storage commodities needs to be considered. The aims of this study were to evaluate endophytic bacteria isolated from rice tissues that inhibit Aspergillus spp. growth, as well as to characterize the selected isolates morphologically and biochemically. Dual culture and disk diffusion method tests on 155 endophytic bacteria obtained three isolates, i.e. FB-Endo 65, FB-Endo 73, and FB-Endo 95, which showed inhibition zone from 13 to 17 mm against Aspergillus spp. growth. The inhibition zone and quantity of antifungal compounds increased positively with the length of incubation periods from 0 to 6 days. Antifungal compounds from the three isolates were insoluble in ethyl acetate, but soluble in methanol. The methanol soluble substance(s) from FB-Endo 73 showed higher inhibition zone than that of the other isolates. This result indicated that all three isolates produced strong antifungal activity. Morphological and biochemical identifications of the isolates revealed that all isolates belonged to the genus Bacillus sp. Further studies include identification and production methods of antifungal compounds of those endophytic bacteria and their application on stored seeds.